Data needs for food policy in developing countries: New directions for household surveys - von Braun, Joachim; Puetz, Detlev (International Food Policy Research Institute, 1993)
Food policy reforms have dominated the development agenda in many low-income countries in recent years. Governments in developing countries as well as donors are becoming increasingly concerned about the impact of policies on people's living standards, food security, and nutrition. The World Summit for Children in 1990 and the International Conference on Nutrition in 1992 as well as the country-level preparation and follow-up activities to these conferences are cases in point.